The social setting of Jesus" exaltation in Luke-Acts (Lk 22:69 and Ac 7:56) - Loba-Mkole, Jean-Claude (HTS teologiese studies, 2005)
This article presents a model for “intercultural exegesis” and applies this model to Luke 22:69 and Acts 7:56. In this process, the term “Son of Man” is approached from two perspectives: that of a biblical culture in the first century Graeco-Roman world, and that of a current Christian culture in Africa. The study concludes that the “Son of Man” concept in the selected texts not only includes a reference to the eschatological saviour, judge and defender, but also creates a sense of Jesus’ solidarity with his fellow human beings. Such an understanding would certainly have led to Jesus’ exaltation by his followers, who lived under conditions of social turmoil in the Graeco-Roman world of the first century, and would lead to such an exaltation by those who experience similar circumstances in Africa today.